Epidemiological profile of Congenital Syphilis in the state of Bahia in the year 2020 (Research, Society and Development, 2022)
Objective: To evaluate the epidemiological profile of congenital syphilis in Bahia in the year 2020. Methodology: Retrospective epidemiological research on cases of congenital syphilis in the state of Bahia, in 2020, with a quantitative approach. Data collection was performed through the National System of Diseases and Notification (SINAN), available at the Department of Informatics of the SUS (DATASUS). Results and Discussion: In 2020, 247 cases of congenital syphilis were reported in children under one year of age. Regarding maternal characteristics, the predominant age group was from 20 to 29 years old (51.4%), followed by adolescents aged between 15 and 19 years old (22.1%). Regarding race, most women were brown (73.9%) followed by black women (10.8). As for schooling, it is noteworthy that 35% of this information is ignored, then 20.9% of women had incomplete Elementary School (5th to 8th grade) and only 0.8% had Completed Higher Education. Conclusion: There was a predominance of syphilis in pregnant women in specific population groups, such as brown and black women, aged between 20 and 29 years old and with a low level of education, in which the majority, despite performing prenatal care, did not perform an appropriate treatment. From this, there is a need for interventions through health programs for prevention, diagnosis and treatment, in addition to the universalization of such offers, so that they cover all population groups.